Acute Hepatitis B Progression to Chronicity - A Prospective Study at Tertiary Care Centre of Northeren India - Malhotra, Parveen; Malhotra, Vani; Sanwariya, Yogesh; Pahuja, Isha; Chugh, Ajay; Akshay (Journal of Hematology Research, 2020)
Background: There are limited number of studies providing information regarding the progression of acute hepatitis B virus (HBV) infection to chronic phase. Aim: To determine the percentage of patients of acute hepatitis B who progressed to chronic hepatitis B stage. Methods: It was a prospective study over a period of four years in which total 409 confirmed acute hepatitis B patients were enrolled but out of them only three hundred and four, (221 men and 83 women, 06–82 years old) were followed regularly for at least six months or more, thus data pertaining to them was analyzed. Results: Out of total of 304 acute hepatitis B patients, 279 patients resolved and became Hepatitis B surface antigen (HbsAg) and Hepatitis B virus DNA negative whereas 25 patients went into chronic phase. No differences were found between groups with respect to age and sex. However, Serum Bilirubin, Serum amino transaminases, HbeAg and HBV DNA Quantitative levels were significantly lower in patients who progressed to chronic hepatitis stage. Conclusions: Around 91.78% of acute hepatitis B patients resolved but 8.22% progressed to Chronic hepatitis B stage The twenty five patients who progressed to chronic infection had mild hepatitis on comparison to 279 patients who resolved, thus suggesting that patients with mild acute hepatitis B infection may have a higher risk of progressing to chronic infection.